Copper chromium oxide spinel, resin composition thereof, resin molded article, and method for producing copper chromium oxide spinel

By using molybdenum compounds as flux in the manufacturing process of copper oxide spinel, the particle size and molybdenum content is controlled, the problem of poor particle size of copper oxide spinel in the prior art is solved, and the plating is improved The performance and catalytic activity achieve the stability and efficient plating effect of resin molded products.

CN119233949APending Publication Date: 2024-12-31DIC CORP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202380040620.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-02
Filing Date
2023-05-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the particle diameter control of copper oxide chromium spinel is poor, resulting in unstable plating performance in resin molded products, and the problem of metal wiring peeling is prone to occur.

Method used

By using molybdenum compounds as flux, molybdenum compounds are added during the calcination of copper and chromium compounds, the particle size and molybdenum content of copper oxide spinel are controlled, and the molybdenum content is ensured by X-ray fluorescence analysis and X-ray photoelectron spectroscopy. The content and distribution form copper oxide chromium spinel with excellent catalyst activity and plating adsorption properties.

Benefits of technology

It realizes precision control of particle diameter, improves plating adsorption performance and catalyst activity, simplifies the production process, and improves the plating adsorption and stability of resin molded products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119233949A_ABST
    Figure CN119233949A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a copper-chromium oxide spinel having a particle diameter suitable for use in the production of a resin molded article, and having plating bonding properties; a resin composition thereof; a resin molded article; and a method for producing the copper-chromium oxide spinel. Specifically, provided is a copper chromium oxide spinel characterized by containing molybdenum and having a D50 of 2.0 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper chromium oxide spinel containing molybdenum and a method for producing the same, and further relates to a resin composition containing the copper chromium oxide spinel, a thermoplastic resin or a thermosetting resin, and an inorganic filler, and a molded product thereof. Background Art

[0002] In recent years, the fields of electronics and mechatronics have been promoting the miniaturization, lightweighting, and multifunctionalization of equipment. In particular, in the automotive field, connectivity, service, and automation are being promoted, and sensors or modules are increasing. On the other hand, the weight of the vehicle is required to be suppressed towards electrification, and there is a strong demand for lightweight and miniaturization of mechanical parts and electrical circuit parts. As a technology that can cope with this, technologies related to molded circuit parts (molded interconnect devices (MID)) have attracted attention. The so-called MID is a technology for molding circuits, electrodes, etc. on resin molded products. By integrating circuits, electrodes, etc. with resin molded products, it is possible to achieve miniaturization and lightweighting of parts.

[0003] MID includes: a one-shot molding method in which the surface of a resin molded product is roughened and then plated; a two-shot molding method in which a circuit-forming resin and an insulating portion-forming resin are molded twice and integrated; and a hot stamping method in which a circuit is directly formed in a resin molded product using a die.

[0004] Among these, laser direct structuring (LDS) technology, which is a one-step forming method, has attracted particular attention from the perspectives of reducing manufacturing costs and being able to produce ultra-fine circuits in a short period of time. In addition, the so-called LDS technology is a technology that can form a strong plating layer on the laser irradiated part by roughening the surface of the laser irradiated part and activating the additive when a resin molded product containing a specified additive is irradiated with laser.

[0005] Therefore, research on additives applicable to LDS technology is being promoted. As additives, spinel metal oxides are generally used (Patent Document 1, Patent Document 2). In particular, from the perspective of adhesion to copper-plated patterns, spinel metal oxides containing copper can be flexibly utilized.

[0006] Patent Document 1 discloses a conductor track structure comprising: a high oxide having a spinel structure that is highly thermally stable and durable in an acidic or alkaline aqueous metallizing electrolyte, or a simple d-metal oxide or a mixture thereof, or a mixed metal oxide similar to a spinel structure.

[0007] Patent document 2 shows a thermosetting resin composition for LDS, which includes a non-conductive metal compound, which includes one or more selected from the group consisting of spinel metal oxides, metal oxides having two or more transition metal elements selected from Groups 3 to 12 of the periodic table and adjacent to the groups, and tin-containing oxides, and forms a metal core by irradiation with active energy lines.

[0008] However, in resin compositions containing these metal oxides, there is a problem that metal wiring after plating sometimes peels off from the molded product. As factors for this, the particle shape or particle diameter of the metal oxide is not sufficiently controlled to be uniformly dispersed in the resin, and the metal oxide that serves as the core of the plating precipitation has a weak bonding force with the plating metal.

[0009] Patent Document 3 discloses a method for producing a copper-chromium black agent as follows: chromium oxide is mixed with copper oxide, zinc oxide, and molybdenum oxide in a ratio of 52% to 75%: 22% to 44%: 1% to 6%: 0.1% to 4%, solid-phase sintering is performed at 820° C. to 960° C. for 1 to 3 hours, and D99 is adjusted to 5 μm to 5.5 μm by ball milling. However, the obtained particles have reduced crystallinity due to the pulverization, and the particle size is still large, so they are not suitable as additives for LDS.

[0010] In non-patent document 1, as a method for producing CuCr2O4 particles, a method for producing CuCr2O4 spinel nanoparticles is shown, which has the following steps: stirring copper nitrate trihydrate and chromium nitrate nonahydrate in pure water, adding ammonia solution to adjust the pH to 8, adding CTAB ethanol solution and hydrazine to prepare a molar ratio of Cu:Cr:CTB:H2O:hydrazine of 1:2:0.75:250:1; a step of hydrothermally treating the solution at 180°C and normal pressure in an autoclave container for 24 hours; and a step of drying the obtained solid product at 120°C and calcining it at 750°C in the air for 6 hours. However, the obtained particles are microparticles of less than 100 nm, which are too small to be used as an additive for LDS.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Publication No. 2004-534408

[0014] Patent Document 2: International Publication No. 2017 / 199639

[0015] Patent Document 3: China Patent Application Publication No. 110951281

[0016] Non-patent literature

[0017] Non-patent document 1: "Catalyst Science and Technology (Catal. Sci. Technol.)", 2014, 4, 4232-4241 Summary of the invention

[0018] Problems to be solved by the invention

[0019] Therefore, the present invention has been made to solve the above-mentioned problems and provides a copper chromium oxide spinel having a particle diameter controlled by a simple method and a method for producing the same.

[0020] Technical means of solving problems

[0021] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that the particle size of copper chromium oxide spinel can be easily controlled by using a molybdenum compound as a flux, and copper chromium oxide spinel containing molybdenum can be produced, thereby completing the present invention.

[0022] That is, the present invention has the following aspects.

[0023] (1) A copper chromium oxide spinel, comprising molybdenum and having a D50 of 2.0 μm or less.

[0024] (2) The copper chromium oxide spinel according to (1), wherein the molybdenum content in the copper chromium oxide spinel is 0.05 mass % to 5.0 mass % in terms of the content (Mo1) calculated as MoO3 relative to 100 mass % of the copper chromium oxide spinel as determined by X-ray fluorescence (XRF) analysis of the copper chromium oxide spinel.

[0025] (3) The copper chromium oxide spinel according to (1) or (2), wherein the molybdenum content in the surface layer of the copper chromium oxide spinel is 0.05 mass % to 15.0 mass % in terms of the content (Mo2) calculated as MoO3 relative to 100 mass % of the surface layer of the copper chromium oxide spinel, as determined by surface analysis of the copper chromium oxide spinel by X-ray photoelectron spectroscopy (XPS).

[0026] (4) A copper chromium oxide spinel according to any one of (1) to (3), wherein the surface-biased molybdenum content (Mo2) calculated on a MoO3 basis with respect to 100 mass % of the surface of the copper chromium oxide spinel relative to the content (Mo1) calculated on a MoO3 basis with respect to 100 mass % of the copper chromium oxide spinel is greater than 2.0.

[0027] (5) The copper chromium oxide spinel according to any one of (1) to (3), wherein the average particle diameter is 0.1 μm to 10 μm.

[0028] (6) The copper chromium oxide spinel according to any one of (1) to (5), wherein the specific surface area measured by the Brunauer-Emmett-Teller (BET) method is 0.01 m 2 / g~10m 2 / g.

[0029] (7) A method for producing copper chromium oxide spinel, wherein the copper chromium oxide spinel is the copper chromium oxide spinel according to any one of (1) to (6), and the method for producing the copper chromium oxide spinel comprises calcining a copper compound and a chromium compound in the presence of a molybdenum compound.

[0030] (8) The method for producing copper chromium oxide spinel according to (7) above, wherein the molybdenum compound is molybdenum trioxide.

[0031] (9) A resin composition comprising: the copper chromium oxide spinel according to any one of (1) to (7);

[0032] Thermoplastic resin or thermosetting resin; and

[0033] Inorganic fillers.

[0034] (10) A resin molded product obtained by molding the resin composition according to (9) above.

[0035] Effects of the Invention

[0036] According to the present invention, copper chromium oxide spinel with controlled particle size can be provided.

[0037] In addition, the present invention can provide a method for producing the copper chromium oxide spinel that is simple and highly productive.

[0038] Furthermore, the present invention can provide a resin composition containing the copper chromium oxide spinel and a molded product thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] [ Figure 1] is the SEM image of the copper chromium oxide spinel of Example 1.

[0040] [ Figure 2 ] is the SEM image of the copper chromium oxide spinel of Example 2.

[0041] [ Figure 3 ] is the SEM image of the copper chromium oxide spinel of Example 3.

[0042] [ Figure 4 ] is a SEM image of the copper chromium oxide spinel of Comparative Example 1. DETAILED DESCRIPTION

[0043] Hereinafter, embodiments of the copper chromium oxide spinel, a method for producing the copper chromium oxide spinel, and a resin composition containing the copper chromium oxide spinel according to the present invention will be described.

[0044] <Copper chromium oxide spinel>

[0045] The copper chromium oxide spinel of the embodiment contains molybdenum. The copper chromium oxide spinel of the embodiment contains molybdenum and has excellent characteristics such as catalytic activity derived from molybdenum.

[0046] The molybdenum contained in the copper chromium oxide spinel of the embodiment is not particularly limited in its existence state or amount, and may be contained in the copper chromium oxide spinel as molybdenum oxide or a partially reduced molybdenum compound, etc., in addition to being molybdenum metal. Molybdenum is considered to be contained in the copper chromium oxide spinel in the form of MoO3, but in addition to being contained in the copper chromium oxide spinel in the form of MoO3, it may also be contained in the copper chromium oxide spinel in the form of MoO2 or MoO, or molybdate, etc.

[0047] The form in which molybdenum is contained is not particularly limited, and it may be contained in a form attached to the surface of the copper chromium oxide spinel, in a form replacing a part of the crystal structure of the copper chromium oxide spinel, in an amorphous state, or in a combination thereof.

[0048] In this specification, the particle shape is controlled, which means that the particle shape is not amorphous. That is, the copper chromium oxide spinel with controlled particle shape in this specification means the copper chromium oxide spinel with non-amorphous particle shape.

[0049] Regarding the copper chromium oxide spinel of the embodiment, the particle size or molybdenum content of the obtained copper chromium oxide spinel can be easily controlled by controlling the amount or type of the molybdenum compound used as a raw material, the calcination temperature, etc. in the production method described below.

[0050] The average particle size of the copper chromium oxide spinel of the embodiment may be 0.1 μm to 10 μm, preferably 0.1 μm to 2 μm, and more preferably 0.1 μm to 1 μm. The average particle size within the above range is preferred because the plating adsorption performance is improved when the resin composition for LDS is prepared.

[0051] In this specification, the so-called "average particle diameter" of copper chromium oxide spinel is calculated as the ratio (shortest diameter / longest diameter) of the shortest diameter (shortest diameter: the shortest distance when each particle is sandwiched by two parallel line segments on the observation field or on its image) and the longest diameter (longest diameter: the longest distance when each particle is sandwiched by two parallel line segments on the observation field or on its image) of the primary particles of copper chromium oxide spinel in a two-dimensional image taken by a scanning electron microscope (SEM).

[0052] The value of the average particle size of the copper chromium oxide spinel is set to be an average value obtained from 50 or more copper chromium oxide spinels randomly selected from the particles having an euhedral shape as the measurement object.

[0053] The median diameter D50 of the copper chromium oxide spinel of the embodiment calculated by the laser diffraction-scattering method may be 2.0 μm or less, 0.2 μm to 2.0 μm, or 1.0 μm to 2.0 μm. The above range is preferred because the plating adsorption performance is improved when the LDS resin composition is prepared.

[0054] The median particle size D50 calculated by the laser diffraction-scattering method of the copper chromium oxide spinel sample can be obtained as a particle size at which the volume cumulative % ratio is 50% in a particle size distribution measured by a dry method using a laser diffraction particle size distribution analyzer.

[0055] The specific surface area of ​​the copper chromium oxide spinel according to the embodiment determined by the BET method may be 0.01 m 2 / g~10m 2 / g, also 1m 2 / g~10m 2 / g, also 3.5m 2 / g~10m 2 When the content is within the above range, the number of active points increases, and the catalyst performance and plating adsorption performance are improved, which is preferred.

[0056] The specific surface area is measured using a specific surface area meter (e.g., BELSORP-mini, manufactured by Microtrac-BEL Co., Ltd.), and the surface area per 1 g of the sample measured based on the amount of nitrogen adsorbed by the BET method (Brunauer-Emmett-Teller method) is taken as the specific surface area (m 2 / g) to calculate.

[0057] The copper chromium oxide spinel of the embodiment contains copper chromite.

[0058] The copper chromium oxide spinel of the embodiment preferably contains 90 mass % to 99.9 mass % of CuCr2O4 relative to 100 mass % of the copper chromium oxide spinel, more preferably 95 mass % to 99.9 mass %, and even more preferably 98 mass % to 99.9 mass %.

[0059] The copper chromium oxide spinel of the embodiment contains molybdenum. The molybdenum content contained in the copper chromium oxide spinel can be measured by XRF analysis. The content (Mo1) obtained by XRF analysis of the copper chromium oxide spinel of the embodiment is preferably 0.05 mass % or more, more preferably 0.05 mass % to 5.0 mass %, and further preferably 0.1 mass % to 2.5 mass %.

[0060] In the XRF analysis, a fluorescent X-ray analysis device (for example, Primus IV manufactured by Rigaku Co., Ltd.) can be used.

[0061] The content (Mo1) calculated by MoO3 conversion refers to the value obtained by converting the molybdenum content obtained by XRF analysis of copper chromium oxide spinel according to the calibration curve converted by MoO3. In addition, the content (Mo1) is the content (Mo1) relative to 100% by mass of the copper chromium oxide spinel.

[0062] The molybdenum content contained in the surface layer of the copper chromium oxide spinel can be measured by X-ray photoelectron spectroscopy (XPS) surface analysis. The molybdenum content in the surface layer of the copper chromium oxide spinel of the embodiment is preferably 0.05 mass % or more, and preferably 0.05 mass % to 15.0 mass %, more preferably 1.0 mass % to 10.0 mass %, and further preferably 1.0 mass % to 7.0 mass %. By being within the range, the copper of the copper chromium oxide spinel exposed by laser irradiation is more activated, and plating is easy to combine, so it is preferred. In addition, by being within the range, for example, the activity of the functional side rings of carbonyl compounds and aromatic compounds as hydrogenation catalysts is increased, so it is preferred.

[0063] In the XPS analysis, a scanning X-ray photoelectron spectrometer (for example, QUANTERA SXM manufactured by Ulvac-phi) can be used.

[0064] The content (Mo2) mentioned above refers to the following value: by performing XPS surface analysis on copper chromium oxide spinel, obtaining the existence ratio (atom %) of each element, converting the molybdenum content into oxide, and thus calculating the MoO3 content relative to 100 mass % of the surface layer of the copper chromium oxide spinel.

[0065] In the copper chromium oxide spinel of the embodiment, it is preferred that the molybdenum is preferentially present in a surface layer of the copper chromium oxide spinel.

[0066] Here, the term "surface layer" in this specification means within 10 nm from the surface of the copper chromium oxide spinel of the embodiment. This distance corresponds to the detection depth of XPS used for measurement in the examples.

[0067] Here, “existing predominantly in the surface layer” means a state in which the mass of molybdenum or the molybdenum compound per unit volume of the surface layer is greater than the mass of molybdenum or the molybdenum compound per unit volume of the area other than the surface layer.

[0068] In the copper chromium oxide spinel of the present invention, molybdenum is preferentially present in the surface layer of the copper chromium oxide spinel, as shown in the examples described later, and can be confirmed in the following manner, that is, the molybdenum content (Mo2) calculated on the basis of MoO3 relative to 100 mass % of the surface layer of the copper chromium oxide spinel obtained by performing XPS surface analysis on the copper chromium oxide spinel is greater than the molybdenum content (Mo1) calculated on the basis of MoO3 relative to 100 mass % of the copper chromium oxide spinel obtained by performing XRF (fluorescent X-ray) analysis on the copper chromium oxide spinel.

[0069] In the copper chromium oxide spinel of the embodiment, as an indicator that molybdenum is preferentially present in the surface layer of the copper chromium oxide spinel, the surface-preferred molybdenum content (Mo2 / Mo1) of the copper chromium oxide spinel of the embodiment (Mo2) obtained by XPS surface analysis relative to the content (Mo1) obtained by XRF analysis is preferably greater than 1.0, more preferably greater than 2.0, particularly preferably greater than 10, and preferably less than 300, more preferably less than 50, and further preferably less than 30.

[0070] By making molybdenum or a molybdenum compound exist preferentially in the surface layer of copper chromium oxide spinel, it is possible to efficiently impart excellent characteristics such as catalytic activity, compared with a case where molybdenum or a molybdenum compound exists uniformly not only in the surface layer but also outside the surface layer (inner layer).

[0071] In addition, the copper content contained in the copper chromium oxide spinel of the embodiment can be measured by XRF analysis. The content (Cu1) obtained by XRF analysis of the copper chromium oxide spinel of the embodiment is preferably 25.0 mass % or more, more preferably 30.0 mass % to 40.0 mass %, and further preferably 32.0 mass % to 35.0 mass %.

[0072] The so-called CuO-converted content (Cu1) refers to the value obtained by converting the copper content obtained by XRF analysis of copper chromium oxide spinel according to the calibration curve using CuO conversion. In addition, the content (Cu1) is the content (Cu1) relative to 100% by mass of the copper chromium oxide spinel.

[0073] The copper content contained in the surface layer of the copper chromium oxide spinel can be measured by XPS surface analysis. The copper content in the surface layer of the copper chromium oxide spinel of the embodiment is preferably 50.0 mass % or more, preferably 55.0 mass % to 80.0 mass %, and more preferably 60.0 mass % to 75.0 mass %. By being within the range, there is a large amount of copper in the copper chromium oxide spinel activated by laser irradiation, and plating is easy to combine, so it is preferred.

[0074] The content (Cu2) refers to the following value: by performing XPS surface analysis on copper chromium oxide spinel, obtaining the existence ratio (atom %) of each element, converting the copper content into oxides, and thus calculating the CuO content relative to 100 mass % of the surface layer of the copper chromium oxide spinel.

[0075] In the copper chromium oxide spinel of the embodiment, it is preferred that the copper is preferentially present in a surface layer of the copper chromium oxide spinel.

[0076] Here, “existing predominantly in the surface layer” refers to a state in which the mass of copper or the copper compound per unit volume of the surface layer is greater than the mass of copper or the copper compound per unit volume of the area outside the surface layer.

[0077] In the copper chromium oxide spinel of the present invention, copper is preferentially present in the surface layer of the copper chromium oxide spinel, as shown in the examples described later, and can be confirmed in the following manner, that is, the copper content (Cu2) calculated on a CuO basis relative to 100 mass % of the surface layer of the copper chromium oxide spinel obtained by performing XPS surface analysis on the copper chromium oxide spinel is greater than the copper content (Cu1) calculated on a CuO basis relative to 100 mass % of the copper chromium oxide spinel obtained by performing XRF analysis on the copper chromium oxide spinel.

[0078] In the copper chromium oxide spinel of an embodiment, as an indicator that copper is preferentially present in the surface layer of the copper chromium oxide spinel, the surface-preferred copper content (Cu2 / Cu1) of the copper chromium oxide spinel of an embodiment, which is the content (Cu2) obtained by XPS surface analysis relative to the content (Cu1) obtained by XRF analysis, is preferably greater than 1, more preferably greater than 1.5, particularly preferably greater than 1.7, and preferably less than 3, more preferably less than 2.5.

[0079] By making copper or copper compounds tend to be present in the surface layer of copper chromium oxide spinel, compared with the case where copper or copper compounds are uniformly present not only in the surface layer but also outside the surface layer (inner layer), the copper of the activated copper chromium oxide spinel is exposed in large quantities on the surface by laser irradiation, resulting in an increase in the number of bonding points with the plating, thereby improving the adhesion of the plating and thus being preferred.

[0080] The copper chromium oxide spinel of the embodiment can be provided as an aggregate of copper chromium oxide spinels, and the values ​​of the molybdenum content and the copper content can be values ​​obtained using the aggregate as a sample.

[0081] The copper chromium oxide spinel of the present invention may contain sodium or potassium in addition to molybdenum.

[0082] <Method for producing copper chromium oxide spinel>

[0083] The method for producing copper chromium oxide spinel of the embodiment includes calcining a copper compound and a chromium compound in the presence of a molybdenum compound. More specifically, the method of the present invention is a method for producing the copper chromium oxide spinel, which may include mixing a copper compound, a chromium compound, and a molybdenum compound to form a mixture, and calcining the mixture.

[0084] By calcining the copper compound and the chromium compound in the presence of the molybdenum compound, copper chromium oxide spinel of a single composition can be produced more efficiently than when no molybdenum compound is used, and the particle diameter can be easily controlled.

[0085] The copper chromium oxide spinel of the above-described embodiment can be produced by the method for producing the copper chromium oxide spinel of the embodiment.

[0086] A preferred method for producing copper chromium oxide spinel includes: a step of mixing a copper compound, a chromium compound, and a molybdenum compound to prepare a mixture (mixing step); and a step of calcining the mixture (calcining step).

[0087] [Mixing process]

[0088] The mixing step is a step of mixing the copper compound, the chromium compound, and the molybdenum compound to prepare a mixture.

[0089] The mixing method is not particularly limited, and simple mixing of powders of the molybdenum compound, the copper compound, and the chromium compound, mechanical mixing using a pulverizer, mixing using a mortar, or mixing in a dry state or a wet state may be used.

[0090] For example, as mixing in a wet state, there is a method of adding a powder of a molybdenum compound, a powder of a copper compound, and a powder of a chromium compound to a liquid medium and mixing them using a stirring mill.

[0091] As the liquid medium, an organic solvent, oil, water or the like can be used, but water is preferred in view of ease of post-treatment.

[0092] The stirring mill is not particularly limited as long as it is a medium stirring mill using a medium medium (beads, balls, sand), and examples thereof include a bead mill, a ball mill, a sand mill, and a paint shaker. In terms of ease of operation, a paint shaker using balls as a medium is preferred.

[0093] From the viewpoint of mixing the raw materials, the stirring time may be 5 to 240 minutes, 30 to 180 minutes, or 60 to 180 minutes.

[0094] For example, as mixing in a dry state, there can be listed manual methods such as putting powders of molybdenum compounds, powders of copper compounds, and powders of chromium compounds into a bag and shaking or kneading them, or using a ball mill, tube mill, vibration mill, planetary mill, etc. with medium media (beads, balls, sand). In terms of ease of operation, a planetary mill with balls as the medium is preferred.

[0095] (Copper compounds)

[0096] The type of the copper compound is not particularly limited. For example, the copper compound may be a monovalent or divalent compound, such as copper chloride, copper sulfate, copper sulfide, copper carbonate, copper oxide, etc., and copper carbonate and copper oxide are preferred from the perspective of easy availability.

[0097] The shape of the calcined copper chromium oxide spinel hardly reflects the shape of the raw copper compound, so as the copper compound, for example, spherical, amorphous, vertically and horizontally structured (wires, fibers, strips, tubes, etc.), sheets, etc. can also be suitably used.

[0098] (Chromium compounds)

[0099] The type of the chromium compound is not particularly limited. For example, examples of the chromium compound include chromium chloride, chromium sulfate, chromium sulfide, chromium carbonate, and chromium oxide. From the viewpoint of easy availability, chromium carbonate and chromium oxide are preferred.

[0100] The shape of the calcined copper oxide chromium spinel hardly reflects the shape of the raw material chromium compound, and therefore, for example, spherical, amorphous, vertically and horizontally structured bodies (wires, fibers, strips, tubes, etc.), sheets, etc. can be suitably used as the chromium compound.

[0101] (Molybdenum compounds)

[0102] Examples of the molybdenum compound include molybdenum oxide, molybdic acid, molybdenum sulfide, molybdenum silicide, silicomolybdic acid, magnesium molybdate, and molybdate compounds, and molybdenum oxide is preferred.

[0103] Examples of the molybdenum oxide include molybdenum dioxide (MoO 2 ) and molybdenum trioxide (MoO 3 ), and molybdenum trioxide is preferred.

[0104] The molybdate compound is only MoO4 2- 、Mo2O7 2- 、Mo3O 10 2- 、Mo4O 13 2- 、Mo5O 16 2- 、Mo6O 19 2- 、Mo7O 24 6- 、Mo8O 26 4- The salt compound of the molybdenum oxide anion is not limited. It can be an alkali metal salt of the molybdenum oxide anion, an alkaline earth metal salt, or an ammonium salt.

[0105] Examples of the molybdate compound include alkali metal salts of molybdenum oxyanions, such as lithium molybdate, potassium molybdate, or sodium molybdate.

[0106] The molybdate compound may be a hydrate.

[0107] The molybdenum compound is preferably at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate, more preferably at least one compound selected from the group consisting of molybdenum trioxide, potassium molybdate, and sodium molybdate, and particularly preferably molybdenum trioxide.

[0108] When a molybdate compound is used, a molybdate compound formed by calcining a mixture of molybdenum oxide and a metal chloride (e.g., a metal carbonate, a halide, a sulfate, etc.) in advance may be used. For example, in the case of sodium molybdate, sodium molybdate formed by calcining a mixture of molybdenum oxide and sodium carbonate may be used.

[0109] As a preferred combination of raw materials in the method for producing copper chromium oxide spinel according to the embodiment, copper oxide, chromium trioxide, and molybdenum trioxide can be used.

[0110] In the method for producing copper chromium oxide spinel of the present invention, a molybdenum compound is used as a flux. In this specification, the production method using a molybdenum compound as a flux is sometimes referred to as a "flux method" below. In addition, through the calcination, the copper compound, the chromium compound, and the molybdenum compound react at a high temperature, and a portion of them forms copper molybdate and chromium molybdate. It is believed that the copper molybdate and chromium molybdate decompose at a higher temperature accompanied by the formation of copper chromium oxide spinel, at which time a portion of the molybdenum oxide is introduced into the copper chromium oxide spinel. A portion of the molybdenum oxide evaporates and is removed outside the system, but in the case of using sodium molybdate or the like as the molybdenum compound, the alkali metal compound is easily combined with the molybdenum oxide to form molybdate again, which is hardly discharged from the system and remains in the system.

[0111] Regarding the formation mechanism of the molybdenum compounds contained in the copper chromium oxide spinel, in more detail, it is believed that in the copper chromium oxide spinel, the reaction of Cu atoms and Cr atoms causes the formation of Mo-O-Cu and Mo-O-Cr, and most of the Mo is released due to high-temperature calcination, but a part of the molybdenum remains in the particles in the state of forming the Mo-O-Cu and Mo-O-Cr.

[0112] The molybdenum oxide that is not introduced into the copper chromium oxide spinel can also be recovered by sublimation and reused. Thus, the amount of molybdenum oxide adhering to the surface of the copper chromium oxide spinel can be reduced, and the original properties of the copper chromium oxide spinel can be maximized.

[0113] On the other hand, the alkali metal salt of the molybdenum oxyanion will not vaporize even in the calcination temperature range and can be easily recovered by washing after calcination. Therefore, the amount of molybdenum compound released outside the calcination furnace is also reduced, and the production cost can be greatly reduced.

[0114] In the flux method, for example, when sodium molybdate is used, copper molybdate and chromium molybdate are decomposed in the presence of liquid sodium molybdate to form copper chromium oxide spinel, which then grows in crystals. As a result, it is believed that copper chromium oxide spinel with low or no aggregation can be easily obtained while suppressing the evaporation of the flux (sublimation of MoO3).

[0115] The effect is assumed to be obtained by replacing sodium molybdate with molybdenum compounds and sodium compounds. It is believed that when a molybdenum compound and a sodium compound are used together, the molybdenum compound and the sodium compound react to form sodium molybdate. Afterwards, in the presence of liquid sodium molybdate, copper molybdate and chromium molybdate decompose to form copper chromium oxide spinel and then crystallize and grow, as described above. As a result, it is assumed that copper chromium oxide spinel with low or no cohesion can be easily obtained while suppressing the evaporation of the flux (sublimation of MoO3).

[0116] In the method for producing copper chromium oxide spinel of the present invention, the amounts of the copper compound, chromium compound, and molybdenum compound used are not particularly limited. In the raw material, for example, in the mixture, the molybdenum compound can be formulated in an amount of 1 to 1000 parts by mass, or in an amount of 5 to 100 parts by mass, relative to 100 parts by mass of the total amount of the copper compound and the chromium compound.

[0117] In the method for producing copper chromium oxide spinel of the present invention, the molar ratio of chromium to copper (Cu / Cr) in the raw material, for example, the mixture, is based on 2, but excess products or raw materials can be easily removed by the refining process described in detail later, so the Cu / Cr can be in the range of 1.5 to 2.5.

[0118] In the method for producing copper chromium oxide spinel of the present invention, the molar ratio of molybdenum atoms in the molybdenum compound in the raw material, for example, the mixture, to copper and chromium atoms in the copper compound and the chromium compound (molybdenum / (copper+chromium)) is preferably greater than 0.001, more preferably greater than 0.005, further preferably greater than 0.01, and particularly preferably greater than 0.02.

[0119] The upper limit of the molar ratio of molybdenum atoms in the molybdenum compound in the raw material, for example, to copper and chromium atoms in the copper compound and chromium compound in the chromium compound can be appropriately determined. However, from the viewpoint of reducing the amount of molybdenum compound used and improving manufacturing efficiency, for example, the value of the molar ratio (molybdenum / (copper+chromium)) may be less than 1, less than 0.5, less than 0.2, or less than 0.1.

[0120] As an example of the numerical range of the molar ratio (molybdenum / (copper+chromium)) in the raw material, for example, in the mixture, the value of molybdenum / (copper+chromium) may be 0.001 to 1, 0.005 to 0.5, 0.01 to 0.2, or 0.02 to 0.1.

[0121] Furthermore, there is a tendency that, as the amount of molybdenum used relative to copper and chromium increases, copper chromium oxide spinel having a smaller primary particle size is obtained as shown in Examples described later.

[0122] By using various compounds within the above range, the amount of the molybdenum compound contained in the obtained copper chromium oxide spinel becomes more appropriate, and the copper chromium oxide spinel having controlled particle shape and particle diameter can be easily obtained.

[0123] (Other additives)

[0124] The method for producing copper chromium oxide spinel according to the embodiment may include a step of calcining a copper compound and a chromium compound in the presence of a molybdenum compound and a sodium compound and / or a potassium compound.

[0125] The method for producing copper chromium oxide spinel of the embodiment may include a step of mixing a copper compound, a chromium compound, a molybdenum compound, and a sodium compound and / or a potassium compound to form a mixture before a calcination step (mixing step), and may include a step of calcining the mixture (calcination step).

[0126] In the production method of the embodiment, by using a sodium compound and / or a potassium compound in combination, the particle size of the copper chromium oxide spinel to be produced can be easily adjusted, and copper chromium oxide spinel with little or no aggregation can be easily produced.

[0127] Here, a compound containing molybdenum and sodium such as sodium molybdate may be used to replace at least a part of the molybdenum compound and the sodium compound. Similarly, a compound containing molybdenum and potassium such as potassium molybdate may be used to replace at least a part of the molybdenum compound and the potassium compound.

[0128] Therefore, the step of mixing a copper compound, a chromium compound, and a compound containing molybdenum and potassium and / or sodium to form a mixture is also regarded as the step of mixing a copper compound, a chromium compound, a molybdenum compound, a potassium compound and / or a sodium compound to form a mixture.

[0129] In addition, the compound containing molybdenum and sodium suitable as a flux can be produced in the process of calcination using molybdenum compounds and sodium compounds, which are cheaper and more easily available, as raw materials. Here, the case of using a molybdenum compound and a sodium compound as a flux and the case of using a compound containing molybdenum and sodium as a flux are combined and regarded as the case of using a molybdenum compound and a sodium compound as a flux, that is, in the presence of a molybdenum compound and a sodium compound.

[0130] The compound containing molybdenum and potassium suitable as a flux can be produced, for example, by using molybdenum compounds and potassium compounds, which are cheaper and more easily available, as raw materials during calcination. Here, the case where a molybdenum compound and a potassium compound are used as flux and the case where a compound containing molybdenum and potassium are used as flux are combined and regarded as the case where a molybdenum compound and a potassium compound are used as flux, that is, in the presence of a molybdenum compound and a potassium compound.

[0131] (Sodium compounds)

[0132] The sodium compound is not particularly limited, and examples thereof include sodium carbonate, sodium molybdate, sodium oxide, sodium sulfate, sodium hydroxide, sodium nitrate, sodium chloride, metallic sodium, etc. Among these, sodium carbonate, sodium molybdate, sodium oxide, and sodium sulfate are preferably used from the viewpoint of industrial availability and ease of handling.

[0133] Furthermore, the sodium compounds may be used alone or in combination of two or more.

[0134] In addition, similarly to the above, sodium molybdate contains molybdenum and thus can also function as the molybdenum compound.

[0135] (Potassium compounds)

[0136] The potassium compound is not particularly limited, and examples thereof include potassium chloride, potassium chlorite, potassium chlorate, potassium sulfate, potassium hydrogen sulfate, potassium sulfite, potassium hydrogen sulfite, potassium nitrate, potassium carbonate, potassium hydrogen carbonate, potassium acetate, potassium oxide, potassium bromide, potassium bromate, potassium hydroxide, potassium silicate, potassium phosphate, potassium hydrogen phosphate, potassium sulfide, potassium hydrogen sulfide, potassium molybdate, potassium tungstate, etc. In this case, the potassium compound contains isomers in the same manner as the molybdenum compound. Among these, potassium carbonate, potassium hydrogen carbonate, potassium oxide, potassium hydroxide, potassium chloride, potassium sulfate, and potassium molybdate are preferably used, and potassium carbonate, potassium hydrogen carbonate, potassium chloride, potassium sulfate, and potassium molybdate are more preferably used.

[0137] Furthermore, the potassium compounds may be used alone or in combination of two or more.

[0138] In addition, similarly to the above, potassium molybdate contains molybdenum and thus can also function as the above-mentioned molybdenum compound.

[0139] (Metal Compounds)

[0140] In the method for producing copper chromium oxide spinel of the embodiment, a metal compound may be used during calcination as needed. The production method may include a step of mixing a copper compound, a chromium compound, a molybdenum compound, and a metal compound to form a mixture before the calcination step (mixing step), and may include a step of calcining the mixture (calcination step).

[0141] The metal compound is not particularly limited, but preferably contains at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.

[0142] Examples of the Group II metal compound include calcium compounds, strontium compounds, and barium compounds.

[0143] Examples of the Group III metal compound include scandium compounds, yttrium compounds, lanthanum compounds, and cerium compounds.

[0144] In addition, the metal compound refers to an oxide, hydroxide, carbonate, or chloride of a metal element. For example, if it is a yttrium compound, yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate can be cited. Among these, the metal compound is preferably an oxide of a metal element. In addition, these metal compounds include isomers.

[0145] Among these, metal compounds of the third period elements, metal compounds of the fourth period elements, metal compounds of the fifth period elements, and metal compounds of the sixth period elements are preferred, metal compounds of the fourth period elements and metal compounds of the fifth period elements are more preferred, and metal compounds of the fifth period elements are further preferred. Specifically, calcium compounds, yttrium compounds, and lanthanum compounds are preferably used, calcium compounds and yttrium compounds are more preferably used, and yttrium compounds are particularly preferred.

[0146] The metal compound is preferably used in a ratio of, for example, 0 mass % to 1.2 mass % (for example, 0 mol % to 1 mol %) relative to the total amount of the chromium compound used in the mixing step.

[0147] [Calcination process]

[0148] The calcining step is a step of calcining the mixture. The copper chromium oxide spinel of the embodiment is obtained by calcining the mixture. As described above, the production method is called a flux method.

[0149] The flux method is classified as a solution method. The so-called flux method, in more detail, is a method of utilizing the crystal-flux two-component system state diagram to show the eutectic crystal growth. As the mechanism of the flux method, it is speculated to be as follows. That is, when the mixture of solute and flux is heated, the solute and flux become a liquid phase. At this time, since the flux is a flux, in other words, since the solute-flux two-component system state diagram shows a eutectic, the solute melts at a temperature below its melting point to form a liquid phase. In the state, if the flux is evaporated, the concentration of the flux decreases, in other words, the melting point reduction effect of the solute brought by the flux is reduced, and the evaporation of the flux becomes a driving force to cause the crystal growth of the solute (flux evaporation method). In addition, the solute and the flux can also cause the crystal growth of the solute by cooling the liquid phase (slow cooling method).

[0150] The flux method has the following advantages: crystal growth can be carried out at a temperature far below the melting point, the crystal structure can be precisely controlled, and a self-shaped crystal can be formed.

[0151] In the manufacture of copper chromium oxide spinel by the flux method using a molybdenum compound as a flux, its mechanism is not necessarily clear, for example, it is speculated to be caused by the following mechanism. That is, when a copper compound and a chromium compound are calcined in the presence of a molybdenum compound, copper molybdate and chromium molybdate are first formed. At this time, as can be understood from the above description, regarding the copper molybdate and chromium molybdate, copper chromite is crystallized and grown at a temperature lower than the melting point of copper chromite. Then, for example, the flux is evaporated, whereby copper molybdate and chromium molybdate are decomposed, and copper chromium oxide spinel can be obtained by crystal growth. That is, the molybdenum compound functions as a flux, and copper chromium oxide spinel is manufactured via the intermediates of copper molybdate and chromium molybdate.

[0152] The flux method can efficiently produce copper chromium oxide spinel containing molybdenum, wherein the molybdenum is preferentially present in the surface layer of the copper chromium oxide spinel.

[0153] The calcination method is not particularly limited and can be carried out by a known and commonly used method. It is believed that during the calcination process, the copper compound, the chromium compound, and the molybdenum compound react to form copper molybdate and chromium molybdate. Furthermore, it is believed that when the calcination temperature reaches 700°C or above, the copper molybdate and chromium molybdate decompose to form copper chromium oxide spinel. In addition, it is believed that in the copper chromium oxide spinel, when copper molybdate and chromium molybdate decompose to form copper oxide, chromium oxide, and molybdenum oxide, and then copper chromite is formed, the molybdenum compound is introduced into the copper chromium oxide spinel.

[0154] The states of the copper compound, the chromium compound, and the molybdenum compound during calcination are not particularly limited as long as the molybdenum compound exists in the same space where it can act on the copper compound and the chromium compound.

[0155] The conditions of the calcination temperature are not particularly limited, and can be appropriately determined in consideration of the particle size of the target copper chromium oxide spinel, the formation of molybdenum compounds in the copper chromium oxide spinel, the shape of the copper chromium oxide spinel, etc. The calcination temperature may be 700° C. or higher, which is close to the decomposition temperature of copper molybdate and chromium molybdate, 800° C. or higher, 900° C. or higher, or 950° C. or higher. When the calcination temperature is high, it is considered to be a factor that the average particle size becomes larger.

[0156] According to the results obtained in the examples described below, when the calcination temperature is 900° C. or higher, copper chromium oxide spinel with controlled particles can be easily obtained.

[0157] Generally, if the shape of the copper chromium oxide spinel obtained after calcination is to be controlled, high-temperature calcination at over 1500°C is required, but this poses a great challenge to industrial use in terms of the burden on the calcination furnace and fuel costs.

[0158] According to one embodiment of the present invention, for example, even under the condition that the maximum calcination temperature for calcining the copper compound and the chromium compound is 1500° C. or less, copper oxide chromium spinel can be efficiently formed at low cost.

[0159] In addition, according to the method for producing copper chromium oxide spinel of the embodiment, copper chromium oxide spinel having a self-shaped shape can be formed regardless of the shape of the precursor even at a temperature much lower than 1500° C. In addition, from the viewpoint of efficiently producing copper chromium oxide spinel, the calcination temperature may be 1500° C. or less, or 1000° C. or less.

[0160] The numerical range of the calcination temperature for calcining the copper compound and the chromium compound in the calcination step may be, for example, 700°C to 1500°C, 800°C to 1200°C, 900°C to 1000°C, or 950°C to 1000°C.

[0161] From the viewpoint of production efficiency, the heating rate may be 20°C / h to 600°C / h, 40°C / h to 500°C / h, 100°C / h to 400°C / h, or 200°C / h to 400°C / h.

[0162] By being within the above range, the particle diameter tends to be controlled.

[0163] Regarding the calcination time, it is preferred that the heating time to the prescribed calcination temperature is within the range of 15 minutes to 10 hours. The holding time at the calcination temperature can be set to more than 5 minutes, preferably within the range of 5 minutes to 30 hours. In order to efficiently form copper oxide chromium spinel, it is further preferred that the calcination temperature holding time is more than 2 hours, and particularly preferably the calcination temperature holding time is 2 hours to 15 hours.

[0164] The calcination environment is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing environment such as air or oxygen, or an inert environment such as nitrogen, argon, or carbon dioxide is preferred. In consideration of cost, an air environment is more preferred.

[0165] The device for calcining is not necessarily limited, and a so-called calcining furnace can be used. The calcining furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and a calcining furnace with high airtightness is preferably used in order to more efficiently utilize the molybdenum oxide.

[0166] [Cooling process]

[0167] The method for producing copper chromium oxide spinel may include a cooling step. The cooling step is a step of cooling the copper chromium oxide spinel after crystal growth in the calcining step.

[0168] The cooling rate is not particularly limited, but is preferably 1°C / hour to 1000°C / hour, more preferably 5°C / hour to 500°C / hour, and further preferably 50°C / hour to 100°C / hour. If the cooling rate is 1°C / hour or more, the manufacturing time can be shortened, so it is preferred. On the other hand, if the cooling rate is 1000°C / hour or less, the calcination container is less likely to be broken due to thermal shock, and can be used for a long time, so it is preferred.

[0169] The cooling method is not particularly limited, and the product may be cooled naturally or by using a cooling device.

[0170] [Post-processing process]

[0171] The method for producing copper chromium oxide spinel of the present invention may further include a post-treatment step of removing at least a portion of molybdenum after the calcining step, if necessary.

[0172] Examples of the method include washing and high temperature treatment, which may be performed in combination.

[0173] In addition, as described above, since molybdenum sublimates during calcination, the molybdenum content in the surface layer of the copper chromium oxide spinel can be controlled by controlling the calcination time, calcination temperature, etc., and the molybdenum content or its existence state outside the surface layer (inner layer) of the copper chromium oxide spinel can be controlled.

[0174] Molybdenum may be attached to the surface of copper chromium oxide spinel. As a method other than the sublimation, the molybdenum may be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or the like.

[0175] At this time, the molybdenum content in the copper chromium oxide spinel can be controlled by appropriately changing the concentration, amount, cleaning location, cleaning time, etc. of the water, ammonia solution, and sodium hydroxide solution used.

[0176] In addition, as a method of high temperature treatment, a method of raising the temperature to a temperature higher than the sublimation point or boiling point of the molybdenum compound can be mentioned.

[0177] [Crushing process]

[0178] The calcined product obtained through the calcination step may be agglomerated and fail to satisfy the appropriate particle size range in the intended application. Therefore, the copper chromium oxide spinel may be pulverized as necessary to satisfy the appropriate particle size range.

[0179] The method for pulverizing the calcined product is not particularly limited, and a conventionally known pulverization method such as a ball mill, a jaw crusher, a jet mill, a disc mill, a Spectromill, a grinder, a mixer mill, etc. can be applied.

[0180] [Grading process]

[0181] In order to adjust the range of particle diameters, the calcined product containing copper chromium oxide spinel obtained by the calcination step may be appropriately subjected to classification. The so-called "classification" refers to an operation of grouping particles according to their sizes.

[0182] The classification may be performed by either a wet method or a dry method, but dry classification is preferred from the viewpoint of productivity.

[0183] In dry classification, in addition to classification using a sieve, there is also wind classification that performs classification based on the difference between centrifugal force and fluid resistance. From the viewpoint of classification accuracy, wind classification is preferred, and can be performed using classifiers such as an airflow classifier utilizing the Coanda effect, a cyclonic airflow classifier, a forced vortex centrifugal classifier, and a semi-free vortex centrifugal classifier.

[0184] The pulverization step or classification step may be performed at a desired stage. The particle size of the copper chromium oxide spinel obtained can be adjusted, for example, by the presence or absence of the pulverization or classification or by selecting the conditions thereof.

[0185] The copper chromium oxide spinel of the embodiment or the copper chromium oxide spinel obtained by the manufacturing method of the embodiment has little or no aggregation, so it is easy to exert its original properties, its own handleability is better, and when it is dispersed in a dispersion medium for use, the dispersibility is better, which is preferred from this point of view.

[0186] In addition, the method for producing copper chromium oxide spinel according to the embodiment can easily produce copper chromium oxide spinel with little or no agglomeration, and thus has the following excellent advantage: even without performing the above-mentioned crushing process or classification process, copper chromium oxide spinel with target excellent properties can be produced with high productivity.

[0187] According to the method for producing copper chromium oxide spinel according to the embodiment described above, it is possible to efficiently produce high-quality copper chromium oxide spinel containing molybdenum and having a controlled shape.

[0188] (use)

[0189] The copper chromium oxide spinel of the present invention contains molybdenum and has a precisely controlled particle size, so it can be suitably used in catalysts or resin compositions. Specifically, it can be used as a synthesis reaction catalyst, an exhaust gas purification catalyst, a heat-resistant pigment, a resin composition for LDS, etc., but is not limited to these.

[0190] <Catalyst>

[0191] The copper chromium oxide spinel of the present invention can be suitably used as a catalyst. Specifically, it can be used as a reaction catalyst used in organic synthesis such as hydrogenation, oxidation, alkylation, and cyclization reactions, volatile organic compounds (VOC), NO x Since the copper chromium oxide spinel of the present invention contains molybdenum, it can have a higher catalytic function than the conventional copper chromium oxide spinel.

[0192] <Resin composition>

[0193] The copper chromium oxide spinel of the present invention can be suitably used in a resin composition. Specifically, as a method for obtaining a resin composition from the copper chromium oxide spinel of the present invention, the resin composition can be obtained in the following manner: using an extruder, a kneader, a roller, etc. as needed, the copper chromium oxide spinel, a thermoplastic resin, and an inorganic filler are fully melt-kneaded until they are uniform, and the kneaded product is cooled. In addition, regarding the shape of the obtained resin composition, when a thermoplastic resin is used, it can be any shape such as granules, and when a thermosetting resin is used, it can be crushed into an appropriate size and made into a flat plate shape by a tablet molding machine, etc.

[0194] The resin composition for LDS may further contain clay minerals, fillers, coupling agents, and other additives as optional components.

[0195] The content of copper chromium oxide spinel in the resin composition relative to 100 parts by mass of the resin composition is contained as a lower limit exceeding 0 parts by mass, preferably 1 part by mass or more, more preferably 5 parts by mass or more, and is preferably less than 30 parts by mass, more preferably less than 20 parts by mass as an upper limit. By being within the above range, the plating property of the obtained molded product can be made good.

[0196] As the thermoplastic resin, there is no particular limitation, and examples thereof include polyester resin, polyarylene sulfide resin, polyamide resin, polyimide resin, polyetherimide resin, polycarbonate resin, polyphenylene oxide resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylene resin, syndiotactic polystyrene resin, polyethylene resin, polypropylene resin, polytetrafluoroethylene resin, polyvinylidene fluoride resin, polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, phenolic resin, carbamate resin, liquid crystal polymer, etc. These resins can be used alone or in combination of two or more. Among these, preferably polyarylene sulfide resin, polyamide resin, polyetherimide resin, polycarbonate resin, polyphenylene oxide resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylene resin, syndiotactic polystyrene resin, in terms of the viewpoint of maintaining the close contact force of plating, particularly preferably polyarylene sulfide resin and polyamide resin with high laser sensitivity.

[0197] As the thermosetting resin, there is no particular limitation, and examples thereof include epoxy resin, phenolic resin, oxetane resin, (meth)acrylate resin, unsaturated polyester resin, diallyl phthalate resin, maleimide resin, etc. These resins can be used alone or in combination of two or more. Among these, epoxy resin is particularly preferred from the viewpoint of improving curability, storage property, heat resistance, moisture resistance, and chemical resistance.

[0198] Relative to the total mass of the resin composition, the thermoplastic resin or the thermosetting resin is preferably in a range of 5% by mass or more, more preferably 10% by mass or more, preferably 40% by mass or less, more preferably 20% by mass or less. If the thermoplastic resin or the thermosetting resin is in a range of 5% by mass or more relative to the total mass of the resin composition, the plating precipitation speed of the obtained molded product can be increased, and therefore it is preferred. In addition, from the perspective of the plating adhesion of the obtained molded product, the filling property or the molding stability, it is preferably 40% by mass or less.

[0199] As the inorganic filler, there can be cited: fused silica, crystalline silica, white silica, aluminum oxide, silicon nitride, aluminum nitride, aluminum hydroxide, boron nitride, titanium oxide, glass fiber, aluminum oxide fiber, zinc oxide, talc, calcium carbide, etc. These inorganic fillers can be used alone, or two or more can be used in combination. From the viewpoint of improving the dispersibility of the resin composition, fused silica and crystalline silica are more preferably used, and from the viewpoint of improving the mechanical strength of the molded product, glass fiber is more preferably used.

[0200] The resin composition may be formulated with a clay mineral as an arbitrary component. The clay mineral and the copper chromium oxide spinel of the present invention play a synergistic role and have the function of improving the plating performance of the obtained molded product and the bonding strength of the plating layer. In terms of obtaining a practical plating precipitation rate for the obtained molded product, the clay mineral is preferably uniformly contained in the resin composition like the copper chromium oxide spinel.

[0201] As the clay mineral, a layered clay mineral having cleavage properties can be used. The clay mineral is not particularly limited, and examples thereof include carbonate minerals and silicate minerals.

[0202] As the filler, there is no particular limitation, and examples thereof include: fibrous fillers such as carbon fiber, silane glass fiber, ceramic fiber, aramid fiber, metal fiber, potassium titanate fiber, silicon carbide fiber, calcium silicate (wollastonite); non-fibrous fillers such as glass beads, glass flakes, barium sulfate, clay, pyrophyllite, bentonite, sericite, magnesium aluminum sepiolite (Attapulgite), ferrite, calcium silicate, calcium carbonate, magnesium carbonate, glass beads, zeolite, and calcium sulfate. These fillers can be used alone or in combination of two or more. These fillers have the function of further imparting mechanical strength to the molded product.

[0203] Examples of the coupling agent include silane coupling agents: epoxy group-containing alkoxysilane compounds such as γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropyltrimethoxysilane, and γ-isocyanatopropyltriethoxysilane. Alkoxysilane compounds containing isocyanate groups such as ethyl dimethoxysilane, γ-isocyanatopropyl ethyl diethoxysilane, and γ-isocyanatopropyl trichlorosilane; alkoxysilane compounds containing amino groups such as γ-(2-aminoethyl)aminopropyl methyl dimethoxysilane, γ-(2-aminoethyl)aminopropyl trimethoxysilane, and γ-aminopropyl trimethoxysilane; alkoxysilane compounds containing hydroxy groups such as γ-hydroxypropyl trimethoxysilane and γ-hydroxypropyl triethoxysilane. These silane coupling agents may be used alone or in combination of two or more. These coupling agents have the function of imparting mechanical strength to molded products in addition to imparting adhesion to different materials.

[0204] Examples of the other additives include hardeners, hardening accelerators, release agents, flame retardants, light stabilizers, heat stabilizers, alkalis, elastomers, titanium oxide, antioxidants, hydrolysis resistance improvers, matting agents, ultraviolet absorbers, nucleating agents, plasticizers, dispersants, antistatic agents, anti-coloring agents, anti-gelling agents, colorants, and the like.

[0205] <Resin molded products>

[0206] The method for obtaining a resin molded product from the resin composition of the present invention is not particularly limited, and a known method can be appropriately adopted, for example, injection molding, injection compression molding, mold molding such as transfer molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, melt molding, etc.

[0207] The obtained molded product is roughened by direct laser molding on the surface or inside, and then plated. The plating can be precipitated only in the roughened area, so it is suitable for use in circuits of built-in antennas or touch sensors and chip packages.

[0208] Laser is a method for roughening the surface layer. The wavelength of the laser can be appropriately selected from the range of 150 nm to 12,000 nm, and is preferably 185 nm, 248 nm, 254 nm, 308 nm, 355 nm, 532 nm, 1,064 nm, or 10,600 nm.

[0209] As a plating treatment, it can be any of electrolytic plating or electroless plating. Through the laser irradiation, the surface layer of the molded product is roughened, and a part of the activated copper oxide chromium spinel in the resin composition is exposed. Thus, during the plating treatment, the plating is only precipitated in the roughened area, so that a circuit can be formed. As a plating solution, there is no particular limitation, and a known plating solution can be used appropriately, and a plating solution containing necessary metal components such as Cu, Ni, and Ag can be used.

[0210] Example

[0211] Next, the present invention will be specifically described by way of examples and comparative examples. Unless otherwise specified, "parts" and "%" are by mass. In addition, copper chromium oxide spinel was synthesized under the following conditions, and was measured or calculated under the following conditions for evaluation.

[0212] <Synthesis of copper chromium oxide spinel>

[0213] (Example 1)

[0214] 7.95 parts of copper (II) oxide (reagent, CuO manufactured by Kanto Chemical Co., Ltd.), 15.20 parts of chromium (III) oxide (reagent, Cr2O3 manufactured by Kanto Chemical Co., Ltd.), 1.16 parts of molybdenum trioxide (manufactured by Japan Inorganic Chemical Industry), 30 parts of ion exchange water, and 120 parts of 5mmφ zirconium oxide beads were placed in a 100ml polypropylene bottle, and mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and the dried product was crushed using a mixer (manufactured by Osaka Chemical). The crushed raw materials were placed in a crucible and calcined at 950°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a black powder. Next, the black powder was dispersed in 300 mL of 0.25% ammonia water, and the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours and passed through a 100 μm sieve. The ammonia water was removed by filtration, and the solution was washed with water and dried to obtain copper chromium oxide spinel.

[0215] (Example 2)

[0216] 7.95 parts of copper (II) oxide (reagent manufactured by Kanto Chemical Co., Ltd., CuO), 15.20 parts of chromium (III) oxide (reagent manufactured by Kanto Chemical Co., Ltd., Cr2O3), 2.32 parts of molybdenum trioxide (manufactured by Nippon Inorganic Chemical Industry Co., Ltd.), and 120 parts of 5 mmφ balls were charged into a planetary mill, mixed and pulverized at 250 rpm for 120 minutes (every 15 minutes), thereby obtaining a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and then pulverized by mixing and pulverizing at 250 rpm for 120 minutes (every 15 minutes). The dried product was pulverized using a mixer (manufactured by Osaka Chemical). The pulverized raw material was placed in a crucible and calcined at 950°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a black powder. Subsequently, the black powder was dispersed in 300 mL of 0.25% ammonia water, and the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours and then passed through a 100 μm sieve. The ammonia water was removed by filtration, and the mixture was washed with water and dried to obtain copper chromium oxide spinel.

[0217] (Example 3)

[0218] Copper chromium oxide spinel was obtained in the same manner as in Example 2 except that the calcination temperature was changed to 900°C.

[0219] (Comparative Example 1)

[0220] 7.95 parts of copper (II) oxide (reagent manufactured by Kanto Chemical Co., Ltd., CuO) and 15.20 parts of chromium (III) oxide (reagent manufactured by Kanto Chemical Co., Ltd., Cr2O3) were placed in a crucible and calcined at 900°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / min. After cooling, the crucible was taken out to obtain a dark green powder. Subsequently, the dark green powder was dispersed in 300 mL of 0.25% ammonia water, and the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours and then passed through a 100 μm sieve. The ammonia water was removed by filtration, and the mixture was washed with water and dried to obtain a dark green powder.

[0221] Compared with Examples 1 to 3, the obtained copper chromium oxide spinel had an incomplete reaction, so the particle size was not controlled within the desired range, and impurities remained. Furthermore, when the resin composition was prepared, it was not uniformly dispersed and did not contain molybdenum, so activation of copper by laser could not be expected, and the adhesion to plating was poor.

[0222] [Crystal structure analysis: X-ray diffraction (XRD) method]

[0223] The sample powder was filled into a measurement sample holder to a depth of 0.5 mm, which was placed in a wide-angle X-ray diffraction (XRD) device (Ultima IV manufactured by Rigaku Co., Ltd.) and measured under the conditions of Cu / Kα rays, 40 kV / 40 mA, a scanning speed of 2° / min, and a scanning range of 10° to 70°.

[0224] [Measurement of specific surface area of ​​copper chromium oxide spinel]

[0225] The specific surface area was measured using a surface area meter (BELSORP-mini, manufactured by Microtrac-BEL Co., Ltd.), and the surface area per 1 g of the sample measured based on the amount of nitrogen adsorption obtained by the BET method was taken as the specific surface area (m 2 / g) to calculate the specific surface area of ​​copper chromium oxide spinel.

[0226] [Median particle size determination]

[0227] The particle size distribution of the sample powder was measured by dry method using a laser diffraction dry particle size distribution meter (HELOS (H3355) & RODOS manufactured by Japan Laser Co., Ltd.) at a dispersion pressure of 3 bar and a tensile pressure of 90 mbar. The particle size at the point where the volume cumulative % distribution curve intersects the horizontal axis of 50% was determined as D50.

[0228] [Average particle size measurement]

[0229] Each sample was observed using a scanning electron microscope (JCM-7000 manufactured by JEOL Ltd.), the particle diameters of 50 particles were randomly measured, and the average value thereof was calculated as the average particle diameter.

[0230] [XRF (X-ray fluorescence) analysis]

[0231] Using a fluorescent X-ray analyzer Primus IV (manufactured by Rigaku Co., Ltd.), about 70 mg of the sample powder was placed on filter paper, covered with a polypropylene (PP) film, and XRF (fluorescent X-ray) analysis was performed under the following conditions.

[0232] Measurement conditions

[0233] EZ Scan Mode

[0234] Determination of elements: F~U

[0235] Measuring time: Standard

[0236] Measuring diameter: 10mm

[0237] Residual ingredients (balance ingredients): None

[0238] The copper content, chromium content, and molybdenum content of the copper chromium oxide spinel obtained by XRF analysis were converted into oxides to obtain the result of the MoO3 content (Mo1) relative to 100% by mass of the copper chromium oxide spinel.

[0239] [XPS surface analysis]

[0240] The surface element analysis of the sample powder was performed by X-ray photoelectron spectroscopy (XPS) using QUANTERA SXM manufactured by Ulvac-phi, Inc., with monochromatized Al-Kα as the X-ray source. The average value of n=3 measurements was obtained for each element in atom % in a 1000 μm square area.

[0241] The copper and chromium contents in the surface layer of the copper chromium oxide spinel and the molybdenum content in the surface layer obtained by XPS analysis were converted into oxides, thereby calculating the MoO3 content (Mo2) (mass %) relative to 100 mass % of the surface layer of the copper chromium oxide spinel.

[0242] [Determination of isoelectric point]

[0243] The zeta potential was measured using a zeta potential measuring device (Malvern, Zetasizer Nano ZSP). 20 mg of the sample was stirred with 10 mL of a 10 mM KCl aqueous solution for 3 minutes using a defoaming stirring taro (Thinky, ARE-310) in stirring / defoaming mode, and the mixture was allowed to stand for 5 minutes. The resulting supernatant was used as a sample for measurement. 0.1 N HCl was added to the sample using an automatic titrator, and the zeta potential was measured in the range of pH = 2 (applied voltage 100 V, Monomodl mode), and the pH at the isoelectric point where the potential becomes zero was evaluated.

[0244] [Table 1]

[0245]

[0246] *Total mass parts of MoO3 relative to 100 mass parts of CuO and Cr2O3

[0247] [Table 2]

[0248]

Claims

1. A copper chromium oxide spinel, characterized in that: Contains molybdenum, and D50 is 2.0 μm or less.

2. The copper chromium oxide spinel according to claim 1, wherein the molybdenum content in the copper chromium oxide spinel is 0.05% by mass to 5.0% by mass, measured by the content (Mo1) calculated as MoO3 relative to 100% by mass of the copper chromium oxide spinel obtained by performing X-ray fluorescence analysis on the copper chromium oxide spinel.

3. The copper chromium oxide spinel according to claim 1 or 2, wherein the molybdenum content in the surface layer of the copper chromium oxide spinel is 0.05% by mass to 15.0% by mass, measured by the content (Mo2) calculated as MoO3 relative to 100% by mass of the surface layer of the copper chromium oxide spinel obtained by surface analysis of the copper chromium oxide spinel by X-ray photoelectron spectroscopy.

4. The copper chromium oxide spinel according to claim 1, wherein the surface-biased molybdenum content (Mo2 / Mo1) of the copper chromium oxide spinel in terms of MoO3 conversion relative to 100 mass % of the copper chromium oxide spinel in terms of MoO3 conversion has a molybdenum content (Mo2 / Mo1) of 2.0 or more.

5. The copper chromium oxide spinel according to claim 1, wherein the average particle size is 0.1 μm to 10 μm.

6. The copper chromium oxide spinel according to claim 1, wherein the specific surface area measured by the Bouert method is 0.01 m 2 / g~10m 2 / g.

7. A method for producing copper chromium oxide spinel, wherein the copper chromium oxide spinel is the copper chromium oxide spinel according to claim 1, and the method for producing the copper chromium oxide spinel comprises calcining a copper compound and a chromium compound in the presence of a molybdenum compound.

8. The method for producing copper chromium oxide spinel according to claim 7, wherein the molybdenum compound is molybdenum trioxide.

9. A resin composition comprising: the copper chromium oxide spinel according to claim 1 or 4; Thermoplastic resin or thermosetting resin; and Inorganic filler.

10. A resin molded product obtained by molding the resin composition according to claim 8.

Citation Information

Cited By

  • Composite oxide particles, method for producing the same, resin composition, and molded body

    WO2026188424A1

  • Composite oxide, method for producing the same, resin composition, and molded body

    WO2026188425A1